Identification of potential hydropower generation sites using geospatial techniques in the Megecha watershed of Ethiopia - Habtamu Wimego Anore; Tarun Kumar Lohani; Abebe Temesgen Ayalew (Heliyon)
The research focuses on modelling the surface water potential using Arc SWAT and Multi-criteria decision-making (MCDM) for selecting the potential hydropower sites in the Megecha watershed. The tenure for stream flow and meteorological data used for SWAT model simulation is from 1990 to 2019 and 1988–2019 respectively. Geospatial method is used to generate gross head and respective potential hydropower. Multi criteria decision method is adopted to select the best site for hydropower generation. Curve number (CN2), saturated hydraulic conductivity (SOL_K), moist bulk density (SOL_BD), and available moisture in the soil layer (SOL_AWC) were among the most sensitive parameters assessed during the research. The performance of SWAT model obtained for R2, NSE and PBIAS were 0.84, 0.78 and −4.6 and 0.81, 0.72 and −4.8 in percentages during calibration and validation periods, respectively. Based on the flow duration curve, the minimum flow of the river for the percent of exceedance of 90 % (Q90) for the sites 1, 2, and 3 are 0.37 m3/s, 0.45 m3/s, and 0.48 m3/s, respectively. The available heads and corresponding hydropower potential on the identified sites were 15, 25, and 20 m and 54.45 KW, 110.36 KW, and 94.18 KW at site1, 2, and 3, respectively. From the GIS based MCDM analysis, the best alternative site for hydropower generation is at site 2, in comparison to identified sites. The total watershed area was 1176 km2 of which, 308.65 million m3 of runoff was generated by the model annually. The watershed has high surface water potential, and the rivers have enough surface water that may be used for hydropower development.